NATIONALISM IN BITHAQAH HAWIYYAH’s POETRY BY MAHMUD DARWISY: RIFFATTERE SEMIOTIC STUDY - Masyitoh, Siti; Haniefa, Rifda; Bahtiar, Ihwan Rahman (Hijai - Journal on Arabic Language and Literature, 2025)
Mahmud Darwisy is a Palestinian poet who has become a Palestinian icon. One of his early poetry collections was Awraq Al-Zaytun (Olive Trees) which included a poetry entitled Bithaqah Hawiyyah (Identity Card). This poetry has a magical power that is strong enough to describe Mahmud Darwisy’s nationalism and the struggle of the Palestinian people to reclaim their homeland which has been colonized by Israel. The theory used is Riffaterre’s semiotic in analyzing this poetry. This research aims to find the elements and forms of nationalism in Bithaqah Hawiyyah’s poetry. The method used is the descriptive-analysis. The conclusion from a semiotic reading of Bithaqah Hawiyyah’s poetry is the fighting or nationalist spirit of the Palestinian people in reclaiming the Palestinian homeland which had been colonized by Israel. The elements of nationalism contained in this poetry are (1) the desire to achieve unity; (2) the desire to achieve independence; (3) the desire to achieve loyalty; (4) the desire to maintain national honor. Furthermore, the forms of nationalism contained in this poetry are (1) civic nationalism and (2) state nationalism. Keywords: Mahmud Darwisy, Poetry, Riffaterre Semiotics, Nationalism.